Broadband extrinsic self-trapped exciton emission in Sn-doped 2D lead-halide perovskites - Yu, Jiancan (2020)
As emerging efficient emitters, metal-halide perovskites offer the intriguing potential to the low-cost light emitting devices. However, semiconductors generally suffer from severe luminescence quenching due to insufficient confinement of excitons (bound electron-hole pairs). Here, Sn-triggered extrinsic self-trapping of excitons in bulk 2D perovskite crystal, PEA2 PbI4 (PEA = phenylethylammonium), is reported, where exciton self-trapping never occurs in its pure state. By creating local potential wells, isoelectronic Sn dopants initiate the localization of excitons, which would further induce the large lattice deformation around the impurities to accommodate the self-trapped excitons. With such self-trapped states, the Sn-doped perovskites generate broadband red-to-near-infrared (NIR) emission at room temperature due to strong exciton-phonon coupling, with a remarkable quantum yield increase from 0.7% to 6.0% (8.6 folds), reaching 42.3% under a 100 mW cm-2 excitation by extrapolation. The quantum yield enhancement stems from substantial higher thermal quench activation energy of self-trapped excitons than that of free excitons (120 vs 35 meV). It is further revealed that the fast exciton diffusion involves in the initial energy transfer step by transient absorption spectroscopy. This dopant-induced extrinsic exciton self-trapping approach paves the way for extending the spectral range of perovskite emitters, and may find emerging application in efficient supercontinuum sources.